Analysis of opportunities and challenges for MSMEs business development through the implementation of sharia marketing strategy - Fuadah, Irma Wardatul; Sulalah, Sulalah; Salsabila, Najwa; Ningsih, Ati’ Lia; Maulana, Ilham (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2024)
Abstract This research aims to identify and analyze the challenges and opportunities in the business of selling young coconuts and siwalan fruit in Pekamban Village, Pragaan District. This business has great potential because young coconuts and siwalan fruit are commodities that are in demand by the public. However, traders often face various obstacles that hinder the growth of their business. The methodology used in this research is a case study method, with a qualitative approach. Data was obtained through in-depth interviews with young coconut and siwalan fruit traders, direct observation in the field, and analysis of related documentation. This research explores various factors that influence sales, such as product quality, price, competition, distribution, and marketing strategies used by traders. The research results show that the main challenges faced by traders include fluctuations in raw material prices, limited capital, intense competition, and lack of knowledge of modern marketing techniques. On the other hand, there are opportunities that can be exploited, such as increasing consumer demand for natural and healthy products, support from local governments, as well as the potential for developing processed products based on young coconuts and siwalan fruit.